Effect of weed control methods and sulphur fertilization on growth and yield of groundnut - Pancholi, Pinki; Yadav, S.S.; Verma, H.P.; Meena, J.S.; Yadav, L.R.; Shivran, A.C. (Annals of Agricultural Research, 2016)
A field experiment was conducted at Agronomy Farm, S.K.N. College of Agriculture, Jobner (Rajasthan) during kharif season of 2013. Results showed that application of pendimethalin at 0.75 kg ha–1 and one HW at 25 days after sowing (DAS) resulted in significant reduction in weed density, weed infestation and weed dry matter in comparison to most of the treatments. The further results indicated that weed free plots showed significantly higher dry matter accumulation, dry weight of nodules per plant, number of pods per plant but number of kernels per pod, seed index, pod yield and haulms yield, remained at par with the application of pendimethalin @ 0.75 kg ha–1. The weed free plot showed significantly higher number of nodules per plant, fresh weight of nodules per plant and remained at par with application pendimethalin @ 0.75 kg ha–1 and one hand weeding at 25 DAS over control. But, weed free plot significantly increased shelling percentage and remained at par with application @ 0.75 kg ha–1, one hand weeding at 25 DAS and imazethapyr @ 100 g ha–1 over control. Result further indicated that application of sulphur @ 60 kg ha–1 significantly higher weed dry matter, dry matter accumulation, dry and fresh weight of nodules, number of nodules per plant, number of pods per plant, number of kernels per pod, seed index, pod yield and haulms yield and shelling percentage over control. However, harvest index, weed density and weed infestation remained materially unchanged under different treatments of weed control and sulphur levels.